Time Synchronization algorithm based on Cluster for WSN - Lei Kong; Qianping Wang; Yan Zhao (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
A Time Synchronization algorithm based on Cluster for WSN was Proposed for WSN (Wireless Sensor Network)- CSSN (Cluster-based Time Synchronization for WSN). The algorithm involved two phases: In the Cluster-inter synchronization phase, it adopted pair-wise packet exchange mechanism to finish the time synchronization between the Base Station and cluster heads through establishing a hierarchical topology structure. Moreover in the Cluster-intra phase, it used reference broadcast mechanism to finish the time synchronization between cluster heads and cluster members. At last, it used linear least square to achieve a good precision. The simulation results showed that the algorithm had faster convergence speed, lower power consumption and better synchronization precision, compared to RBS and TPSN algorithm.